Gender issues in secondary school placement - Leo-Rhynie, Elsa
This paper examines differential ,\y education for Jamaican boys and girls, using data from the Common Entrance Examination (CEE), a selection examination to identify students who will participate in secondary level academic education. It identifies gender issues that have arisen as a result of the CEE and secondary school placement, and discusses implications for Jamaica's development
Keywords: Gender issues